Avifauna de fragmentos de Mata Atlântica da Zona da Mata de Pernambuco, Brasil, com ênfase na estrutura trófica - Telino Júnior, Wallace Rodrigues (2006)
The study of the diet of birds can supply important information on the structure trophic of communities, as well as of the physical conditions of the atmosphere in that you/they live. There are few detailed studies on alimentary items of the Brazilian birds, mainly in the northeast area of Brazil. This work had as general objective to demonstrate the organization trófica in fragments of Atlantic forest in the State of Pernambuco. The registrations of the birds were based on observations in situ, data of the literature, study of the scientific collection of birds of UFPE, besides interviews with residents of the area. The categorization trófica felt through observations of I forage, analysis of the fecal content and data of the literature. This last analysis was just accomplished in the fragments of the Ecological Station of Tapacurá (EET), where the captured birds had their collected feces and analyzed at the laboratory of entomology of UFSCar. During this research 255 species of birds were registered for the three studied fragments. He/she gave total, 225 species were classified for the State Reservation of Gurjaú, 183 species for Camocim and 172 for the Downpour, being distributed in 53 families and 11 subfamilies. Of the general total of the striped birds there was prevalence of the species insetívoras (n = 113), following by the omnivorous ones (n = 65) and of the granívoras (n = 19). In gurjaú the percentile of insetívoras was of 44% and of omnivorous, 26,22%; in Camocim the percentile was from 45,90% to insetívoras and 27,32% for omnivorous; in the fragment of the Downpour 46,51% insetívoras and 29,07% omnivorous. The birds of more specialized diets as the frugivorous ones, appear in third place, with larger number of species in Gurjaú (n = 18), in that you/they stand out those species of larger load, as example: Crypturellus soui, Pionus maximiliani, Pteroglossus aracari and Pteroglossus inscriptus, were observed in all of the Reservation's fragments during the research. However, in Camocim and in the Downpour the number of frugivorous species was very smaller (n = 8 and 7 respectively), being less of the half of that found in Gurjaú; there was not registration of big frugivorous. In Gurjaú, species specialist insetívoras, ant-of-honesty followers and climbers of trunks were observed, and frugivorous of great load. Of the 252 samples of analyzed feces, the species insetívoras prevailed in the results (n = 31), following by those omnivorous ones (n = 8) and frugivorous (n = 6). Among the insetívoras, Tyrannidae (n = 16) it was the family with larger number of species and the subfamily Elaeniinae stands out, representing 68,75%. among the frugivorous ones, only three species of the family Pipridae and three of the subfamily Thraupinae were captured. Among the captured individuals they prevailed the exclusive insetívoros (n = 184), and after, omnivorous (n = 37), frugivorous (n = 28) and granívoros (n = 2). The results of this work demonstrate that the Reservation of Gurjaú presents support capacity to shelter species specialist insetívoras (e.g. Pyriglena leuconota, Conopophaga melanops and Conopophaga lineata) and big frugivorous (e.g. Pionus maximiliani, Pteroglossus aracari and Pteroglossus. inscriptus). The fragments of the Ecological Station of Tapacurá present a smaller number of specialized insetívoros and any big one frugivorous, due to the great alteration antrópica happened in the area and the isolation of the fragments by the monoculture of the sugarcane, impeding or hindering the permanence of more sensitive birds to environmental alterations.